2022
DOI: 10.1007/s11356-022-22119-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the carbon footprint of a Colombian University Campus using the UNE-ISO 14064–1 and WRI/WBCSD GHG Protocol Corporate Standard

Abstract: Higher education institutions (HEIs) transfer skills and knowledge between industries, the government, and the public, playing a vital role at educating future leaders in creating a globally sustainable system. Therein, evaluating greenhouse gas emissions from an educational institute is the first step towards the proposed reduction targets at the local, national, and international levels. In this research, we report the first approximate carbon footprint calculation of emissions corresponding to scope 1, scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…The CF is conventionally presented in terms of 𝐶𝐶𝐶𝐶 2 equivalent mass, which serves as a metric for the total quantity of carbon dioxide emissions directly and indirectly attributed to an undertaking or accumulated over the life cycles of a product. Some of the reported studies of academic institutions or universities regarding carbon footprints are summarized in Table 1 [14][15][16][17][18][19][20][21][22][23][24][25][26][27] along with the computation methods being adopted.…”
Section: Introductionmentioning
confidence: 99%
“…The CF is conventionally presented in terms of 𝐶𝐶𝐶𝐶 2 equivalent mass, which serves as a metric for the total quantity of carbon dioxide emissions directly and indirectly attributed to an undertaking or accumulated over the life cycles of a product. Some of the reported studies of academic institutions or universities regarding carbon footprints are summarized in Table 1 [14][15][16][17][18][19][20][21][22][23][24][25][26][27] along with the computation methods being adopted.…”
Section: Introductionmentioning
confidence: 99%
“…En la figura 2 se observan los principales cambios en las metodologías de cálculo de HC; así, la ISO 14064:2018 describe 6 categorías de medición, entre las emisiones directas (combustibles) e indirectas (electricidad, transporte, uso de productos y análisis de ciclo de vida de productos). La ISO 14064:2018 posee un nuevo enfoque de medición, referido a la categoría 5, que amplía el estudio de cuna a tumba para los bienes utilizados por la organización, por lo que se sigue un enfoque de análisis de ACV de proveedores por insumo o proceso realizado, debido a que estas emisiones resultan de las actividades de terceros asociadas con los insumos utilizados por la organización (Cano et al, 2022).…”
Section: Introductionunclassified
“…These, on the other hand, indicate universities' ability to achieve operational carbon neutrality by reducing scope 1 and 2 emissions by 2030 [49] and scope 3 emissions by 2050, hence becoming zero emission campuses. Cano et al [57] calculated the carbon footprint of emissions corresponding to scopes 1, 2, and 3 of urban Columbian universities. The authors identified the transportation process as the largest source of greenhouse gas emissions (58.51%), followed by the wastewater process (17.01%), electricity consumption (14.03%), and e-mails sent (6.51%).…”
Section: Introduction 1backgroundmentioning
confidence: 99%